The effects of upper lip height on smile esthetics perception in normal occlusion and nonextraction, orthodontically treated females - Jahanbin Arezoo; Pezeshkirad Hossein (Wolters Kluwer Medknow Publications, 2008)
Background: The esthetic of smile is influenced by such features as the amount of incisor show and gingival display. Aims: The purposes of this study were to compare smile esthetics among normal occlusion and non extraction patients, assess upper lip height in two groups and discuss how this feature relate to smile esthetics. Settings and Design: We therefore conducted a case control study to determine the mentioned aims. Materials and Methods: Thirty females with non extraction orthodontically treated occlusions and thirty three with normal occlusions were selected. Standardized black and white photographs of their posed smiles were evaluated by a panel of 5 men and 5 women of varied vocations by use of visual analogue scale. Then upper lip height of the two groups were measured from photographs. Statistical Analysis: Smile esthetics and differences among the two groups were subjected to ANOVA and Mann-whitney test was used to compare upper lip height in them. Results: This study showed that upper lip height did not differ among the 2 groups ( P = 0.98). Also there were no significant differences in the distribution of fair,good and very good smiles among the two groups. Conclusions: This study demonstrates that the non extraction orthodontic treatment does not influence smile esthetics.